2015
DOI: 10.1007/s00267-015-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Interaction in Participatory Land Restoration in Iceland: Environmental Officers’ Challenges and Strategies

Abstract: Participatory approaches involve stakeholder interaction but environmental agency employees engaged in participatory undertakings often lack training for interaction tasks. This study explored how district officers at the Soil Conservation Service of Iceland (SCSI) experienced and dealt with stakeholder interaction in participatory land restoration. We made semi-structured interviews with all district officers with at least 1-year experience; seven in total. A thematic content analysis revealed five challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Demonstrative planting was barely supported by farmers, particularly by those responsible of forest clearing. This confirms previous studies showing that farmers frequently oppose forest restoration actions because of concerns on losses of farming and grazing opportunities (Arnalds ), and also because of unawareness and uncertainty on the role of restoration to improve land condition (Berglund et al ). Previous research focused on restoration has shown a high willingness of local stakeholders to participate in individual meetings, but poor response to collective meetings and limited engagement in implementation tasks because of mistrust and fruitless previous interactions with government agencies (Metcalf et al ).…”
Section: Lessons Learned From the Resep2b Projectsupporting
confidence: 89%
“…Demonstrative planting was barely supported by farmers, particularly by those responsible of forest clearing. This confirms previous studies showing that farmers frequently oppose forest restoration actions because of concerns on losses of farming and grazing opportunities (Arnalds ), and also because of unawareness and uncertainty on the role of restoration to improve land condition (Berglund et al ). Previous research focused on restoration has shown a high willingness of local stakeholders to participate in individual meetings, but poor response to collective meetings and limited engagement in implementation tasks because of mistrust and fruitless previous interactions with government agencies (Metcalf et al ).…”
Section: Lessons Learned From the Resep2b Projectsupporting
confidence: 89%
“…Boundary spanners were regularly cited among the case studies to enable KE work (e.g., Cohen et al, 2012;Berglund et al, 2015;Coleman & Stern, 2018;Holzer et al, 2019;Cadman et al, 2020), which is consistent with the broad literature suggesting that they play a key role in collaborating, facilitating, and exchanging context-specific knowledge with diverse knowledge users (Armitage et al, 2011;Bednarek et al, 2018;Karcher et al, 2021). It is necessary for boundary spanners to possess sufficient background knowledge and expertise of the knowledge they are exchanging (Michaels, 2009;Saarela & Soderman, 2015).…”
Section: Enablers To Effective Ke For Practitionerssupporting
confidence: 56%
“…Many of the challenges to implementing KE were related to the expertise and interpersonal skills of KE practitioners. For example, practitioners had difficulty maintaining trusting relationships with all project actors and sustaining regular communication to identify the evolving needs of knowledge users (e.g., Berglund et al, 2015;Laatsch & Ma, 2016). In the case study produced by Berglund et al (2015), they explored how officers at the Soil Conservation Service of Iceland (SCSI) can improve soil conservation decisions and practices through their interactions with project actors, specifically farmers and locals.…”
Section: Challenges: How Implementing More Enablers Can Help Overcome...mentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges facing the field officers are often complex, as reported by Berglund et al [28]. There is a need for better linkages between the research and science capacity of the SCSI and other agencies involved in the schemes, on one hand, and the people in the field on the other.…”
Section: Discussionmentioning
confidence: 99%